"A Field Study of the Distribution of Entamoeba histolytica / dispar Cyst Passers in Northern, Central, and Southern Iran" - H Hooshyar; M Rezaian1; M Mahmoodi; S Farnia1; Sh Solaymani-Mohammadi (Tehran University of Medical Sciences, 2004)
Amoebiasis is one of the most important human diseases in many countries especially in tropical and sub-tropical regions. This study was carried out from August 1999 to February 2002 in order to determine the ratio of Entamoeba histolytica / Entamoeba dispar in some regions of Iran. A total of 16,592 stool samples were randomly collected from different agegroups in central, northern and southern Iran both from urban and rural areas. The samples were examined by direct and formalin-ether concentration methods. Two hundred and twenty six samples (1.36%) were positive for E. histolytica/E. dispar cyst (C.I = 1.18-1.54%). The prevalence of infection with E. histolytica/E. dispar was 0.78%, 3.9% and 4.6% for central, northern and southern part of Iran, respectively. The minimum rate of prevalence was 0.6% in Tehran, Yazd and Ardekan (central Iran), while the highest rate (8.3%) was seen in rural areas of Ahwaz (southern Iran).The study showed that ratio of E. histolytica /E. dispar was higher in southern regions (tropical and subtropical) than other regions. It seems that more sanitary facilities and health trainings are needed in different parts of the country, especially in southern Iran, where the rate of infection is high.